1983
DOI: 10.1002/fam.810070406
|View full text |Cite
|
Sign up to set email alerts
|

The pyrolysis of organic nitriles

Abstract: Detailed quantitative studies are reported on the kinetics of acetonitrile pyrolysis using an isothermal quartz tubular flow reactor at 720-1033 K and 1 atm. pressure using flow rates, in nitrogen, of 2-200 ml min-'. The pyrolysis of several other nitriles (acrylonitrile, propionitrile, methacrylonitrile and benzonitrile) has also been investigated qualitatively by pyrolysis-gas Chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The yield of HCN was found to increase with temperature, with almost quantitative yields (ca. 94%) reported in the shock tube studies, while lower yields were reported in the flow pyrolysis studies [68% (Chaigneau 1977) and 90% estimated (Metcalfe et al 1983)]. The reaction pathways for the primary products are shown below:…”
Section: Pyrolysismentioning
confidence: 93%
See 3 more Smart Citations
“…The yield of HCN was found to increase with temperature, with almost quantitative yields (ca. 94%) reported in the shock tube studies, while lower yields were reported in the flow pyrolysis studies [68% (Chaigneau 1977) and 90% estimated (Metcalfe et al 1983)]. The reaction pathways for the primary products are shown below:…”
Section: Pyrolysismentioning
confidence: 93%
“…The pyrolysis of acetonitrile (CH 3 CN) has been studied in a tubular flow reactor from 447 to 760°C in nitrogen (Metcalfe et al 1983), in a stirred-flow reactor from 880 to 960°C in helium (Asmus and Houser 1969), and in a shock tube from 1027 to 1827°C in argon with residence times of 0.7-1.7 ms (Lifshitz, Moran, and Bidani 1987;Ikeda and Mackie 1996). In all the studies, the major products from the pyrolysis of acetonitrile were hydrogen cyanide (HCN) and methane (CH 4 ).…”
Section: Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…They found that these compounds were at least in part reacted to yield nitrogen oxides and molecular nitrogen. Metcalfe et al [32][33][34][35] studied the pyrolysis of several nitriles and para-toluene isocyanate to establish mechanisms for the generation of hydrogen cyanide. Chambers and Reese [36][37][38] studied the thermal decomposition of polyurethanes.…”
Section: Small Scale Studiesmentioning
confidence: 99%